2018
DOI: 10.1111/jvim.15305
|View full text |Cite
|
Sign up to set email alerts
|

Survival associated with cerebrospinal fluid analysis in downer adult dairy cows: A retrospective study (2006‐2014)

Abstract: BackgroundThreshold values for total nucleated cell count (TNCC) and protein concentration in cerebrospinal fluid (CSF) of downer dairy cows suggestive of a spinal cord lesion were recently published.ObjectivesDetermine short‐ and long‐term survival of downer cows that underwent CSF analysis using the reported threshold values. Evaluate the prognostic value of these threshold values to predict short‐ and long‐term survival.AnimalsTwo hundred and fourteen downer adult dairy cows that underwent CSF analysis duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Collection and analysis of CSF from animals suffering from spinal cord trauma is valuable for ruling out other causes of acute spinal cord disease, such as viral, verminous, and protozoal myeloencephalitis (Mayhew 2009). In fact, increases in proteins concentrations (>0.39g/L) and nucleated cell counts (>4.5 cells/μL) in the CSF of recumbent cows have been linked to spinal cord injury (Achard et al 2017) and to decreased short-term survival (Bilodeau et al 2018). Accordingly, firm evidence of subarachnoid hemorrhage may not always be found on analysis of CSF in spinal cord trauma (Mayhew 2009), as in our cases.…”
Section: Resultsmentioning
confidence: 56%
“…Collection and analysis of CSF from animals suffering from spinal cord trauma is valuable for ruling out other causes of acute spinal cord disease, such as viral, verminous, and protozoal myeloencephalitis (Mayhew 2009). In fact, increases in proteins concentrations (>0.39g/L) and nucleated cell counts (>4.5 cells/μL) in the CSF of recumbent cows have been linked to spinal cord injury (Achard et al 2017) and to decreased short-term survival (Bilodeau et al 2018). Accordingly, firm evidence of subarachnoid hemorrhage may not always be found on analysis of CSF in spinal cord trauma (Mayhew 2009), as in our cases.…”
Section: Resultsmentioning
confidence: 56%
“…Additionally, experimental studies have suggested that significant pressure damage can occur in the compressed forelimbs as early as 6 hours after sternal recumbency has begun (COX et al, 1982;COX, 1988). Euthanasia has been recommended for nonambulatory cows with more than 24 hours of recumbency (BILODEAU et al, 2018). Therefore, the heifer's overweight condition and non-observance of animals during transportation to avoid recumbency were probably the determinant factors for the development of DCS in this case.…”
Section: Alves Et Almentioning
confidence: 87%
“…Highly productive and older dairy cows are at great risk of developing DCS, which frequently occurs within 24 hours after calving (COX, 1988;BILODEAU et al, 2018;LABONTÉ et al, 2018). Clinical hypocalcemia, stillbirth, and dystocia were identified as risk factors for DCS in dairy cattle during the first 30 days after parturition (CORREA et al, 1993).…”
Section: Alves Et Almentioning
confidence: 99%
See 2 more Smart Citations